Improvement of Erectile Dysfunction by Revascularization Surgery Following Urethroplasty in Patients with Pelvic Fracture - Najd Sepas, Hoss; Tayyebi Azar, Ali; Bashirian, Manouchehr; Mirkazemi, Farhad; Soleimanzadeh, Farzin; Mousavi, Reza; Zolghadr, Zahra; Hosseini, Jalil (Archives of Men’s Health, 2018)
Introduction: Erectile dysfunction is one of the most common sexual disorders in men and affects one out of every five men over the age of 40 years. Penile revascularization is one of the methods for treating erectile dysfunction in these patients. Methods: The participants were patients who had erectile dysfunction after a pelvic fracture. These patients had Urethroplasty for at least one year ago due to urethral trauma and also undergone penile micro vascularization surgery. Sexual activity was allowed from the second month accompanied with the administration of tadalafil and yohimbine prior to intercourse. Results: In this study, 52 patients with the mean age of 30.65 ± 7 years (range: 24-45) were included. 24 patients (46%) were married. The mean time interval between pelvic fracture and surgery was 49.80 ± 16.30 months (range: 22 to 85). Complete response was seen in 9 cases (17.3%), relative responses in 18 (34.6%), and treatment failure in 25 cases (48.1%). The treatment results did not show any significant difference between the two dissimilar surgical procedures (Micheal versus-Virag) (P = 0.58). Conclusion: Based on this case-series, it is concluded that penile revascularization surgery seems to have a relatively good effect on the improvement of vascular erectile dysfunction in patients with pelvic fracture urethral distraction effect following Urethroplasty.